Role of Interventional Radiology in the Management of Massive Hemoptysis - Prijo Sidipratomo; Gabriela Enneria Sibarani (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Massive hemoptysis is one of the emergencies in respiratory system, representing hemorrhage of the bronchial or pulmonary vascular system into the respiratory tract. Massive hemoptysis is a life-threatening condition due to high risk of asphyxia it may induce. Bronchial artery embolization (BAE) is an interventional radiology procedure dedicated in the emergency management of massive hemoptysis. BAE is known for its great success rate and low risk of complications. Proper catheterization technique, recognition of bronchial artery variant anatomy and appropriate selection of embolic material agent proves essential in determining the success of this procedure. As a minimally invasive procedure, BAE is highly recommended to be used in cases of massive hemoptysis.